Prevalence of Pulp Polyp, Fluorosis and Malocclusion in a Known Population - Bagchi, Sanjukta; garg, Shefally; Parameshwaran, V. N.; Sangabathula, Soumya; Rahar, Arun; Chopra, Meenakshi (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Prevalence of Pulp Polyp, Fluorosis and Malocclusion in a Known Population. Material and methods: This study comprised of total 100 participants. The subjects were explained about the study procedure and they were asked to give consent. All the subjects gave consent and hence all the subjects had been included in the study. The prevalence of pulp polyp, fluorosis and malocclusion was assessed. The type of malocclusion was also assessed in the subjects who had malocclusion and the findings were tabulated. Statistical analysis was conducted using SPSS software. Results: In this study, there were total 100 subjects of which 36 subjects had pulp polyp, 35 subjects had fluorosis and 29 subjects had malocclusion. Out of 29 cases of malocclusion, 3 cases were of type I malocclusion, 19 cases were of type II malocclusion and 7 cases were of type III malocclusion. There were total 57 males and 43 females in this study, 19 males and 17 females had pulp polyp. 20 males and 15 females had fluorosis. 18 males and 11 females had malocclusion. Conclusion: From the findings of this study, it can be concluded that the prevalence of pulp polyp, fluorosis and malocclusion was 36%, 35% and 29%, respectively.